QTL mapping for traits at reproductive stage drought stress in rice using single marker analysis - Barik, S R; Pandit, E; Mohanty, S P; Pradhan, S K (ORYZA-An International Journal of Rice, 2018)
Drought is the major abiotic constraint leading to very high yield reduction in both rain-fed upland and lowland areas worldwide. Reproductive stage is the most sensitive to water deficiency as compared to vegetative stage of rice. In this present investigation, association between phenotype and genotype was carried out for the drought mapping population of CR143-2-2/ Krishnahamsa to detect QTLs through single marker analysis (SMA). A total of 21 polymorphic SSR markers were detected through bulked segeregant analysis approach. QTL mapping was performed through ICIM v4.0 software. Only phenotypic trait, days to 50% flowering (DFF) at reproductive stage stress showed association with chromosome 1 and 6. A significant higher peak was obtained in RM3825 marker linked in chromosome 1 detected to be a novel QTL, qDFF1.1 controlling flowering under drought stress. The other QTL on chromosome 6 is validated in this mapping population which controls flowering under terminal drought stress.